1998
DOI: 10.1038/sj.leu.2401021
|View full text |Cite
|
Sign up to set email alerts
|

Secondary acute leukemia and myelodysplastic syndrome with 11q23 abnormalities

Abstract: Forty of the 550 patients (7%) entered to the 11q23 Workshop had secondary (s) acute lymphoblastic leukemia (nine cases), s-acute myeloid leukemia (25 cases, predominantly of FAB type M5), s-acute leukemia unspecified (one case) or s-myelodysplastic syndrome (five cases) following treatment for a primary malignancy. Breast cancer (12 cases) and non-Hodgkin's lymphoma (eight cases) were the most frequent primaries. Twentythree patients had been treated with either an epipodophyllotoxin (seven patients) or an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 20 publications
2
69
0
3
Order By: Relevance
“…56,57 A review of the literature, however, reveals that all published therapy-associated t(4;11)-positive ALL, in which treatment was specified, had received chemotherapy targeting DNA topoisomerase II, ie etoposide, teniposide, doxorubicin, epidoxorubicin and mitoxantrone. 5 A detailed discussion on therapy-related 11q23 malignancies collected by the Workshop, including the present 10 cases, is found in Secker-Walker et al 58 The majority of the 183 cases of leukemia displayed t(4;11) as the sole change; additional, or secondary, changes were seen in only 30% of the cases (Table 1). Previous studies have also shown that t(4;11) usually occurs as the sole anomaly.…”
Section: Discussionmentioning
confidence: 85%
“…56,57 A review of the literature, however, reveals that all published therapy-associated t(4;11)-positive ALL, in which treatment was specified, had received chemotherapy targeting DNA topoisomerase II, ie etoposide, teniposide, doxorubicin, epidoxorubicin and mitoxantrone. 5 A detailed discussion on therapy-related 11q23 malignancies collected by the Workshop, including the present 10 cases, is found in Secker-Walker et al 58 The majority of the 183 cases of leukemia displayed t(4;11) as the sole change; additional, or secondary, changes were seen in only 30% of the cases (Table 1). Previous studies have also shown that t(4;11) usually occurs as the sole anomaly.…”
Section: Discussionmentioning
confidence: 85%
“…The median white blood cell count (WBC) (×10 9 /l) and percentage of blasts in the bone marrow were 58.1 and 50, respectively, for the infants, 44.3 and 90, respectively, for the children and 32 and 95, respectively, for the adults. One patient had a secondary, therapy-related AML, an adult who had received lumbar irradiation, 12 the remainder of patients presented with de novo disease.…”
Section: Patient Data At Diagnosismentioning
confidence: 99%
“…MLL fusion genes are found in precursor-B-ALL, AML, myelodysplastic syndrome (MDS), some cases of T-ALL, and in secondary leukemia. [60][61][62][63][64][65][66] In addition to MLL fusion genes generated by translocations, deletions of exon 11 have been associated with T-ALL 67 and tandem duplications of the gene have been observed in both de novo and secondary AML 68 as well as in normal peripheral blood and bone marrow mononuclear cells. 69 The AF4 gene is composed of 20 exons and encodes a serine-proline-rich protein.…”
mentioning
confidence: 99%